Psychological Eco-Facilitation as a Path to Post-Traumatic Growth: Trauma Integration and Personal Development - Lushyn, Pavlo (Young Scholars Grinchenko – Seton International Journal, 2024)
This article explores the concept of post-traumatic growth through the lens of psychological eco-facilitation, developing approaches to assist individuals who have experienced trauma. Drawing on his experience working with victims of extreme events, including Chornobyl disaster participants and war veterans, P. Lushyn discusses methods for treating post-traumatic stress disorders, emphasizing the importance of personal growth after trauma. He utilizes eco-facilitation principles to support individuals in restoring their ability to dream and plan for the future, a key aspect of post-traumatic growth. A dialogue with artificial intelligence, simulating an eco-facilitation session, demonstrates the dynamics of change in client perception, aiding in understanding the efficacy of this approach.